Recent Advancement and Future Prospects of Plasma Technology for the Quality and Quantity Enhancement of Agricultural Production: Plasma Technology in Agricultural Production - Khan, Md Abdul Helim; Rahman, Md Mahmudur; Tasmima, Tahera; Hossain, Md Alamgir (SAARC Journal of Agriculture, 2025)
An intercrop-based experiment was conducted for two consecutive years, 2020-21 to 2021-22, at a farmer’s field of MLT site, Madhupur, Tangail, to find a suitable intercrop combination of vegetables with bananas for higher productivity and profitability. There were three intercrop-based treatments, i.e., Banana + Potato, Banana +Cabbage+ Potato, and Banana + Cauliflower + Potato, along with Sole banana. A variety of bananas (Amrit Sagar), Cabbage (Parel), Cauliflower (Thirty-three), ranola) were used as Potatoes (G test material. The experiment was laid out in a randomized complete block design with six dispersed replications. The unit plot size was 400 m2. The results revealed that all the intercrops’ treatments produced a higher banana equivalent yield than the sole banana. However, among the intercrop combinations, Banana + Cauliflower + Potato provided the highest equivalent yield (101.89 tha-1 followed by Banana + cabbage + potato, which was 70.42 and 69.52 % higher than the sole crop. Sole banana cultivation produced the lowest banana yield (60.49 t ha-1). The higher gross margin (Tk.666898 ha-1) was also obtained from the Banana + cauliflower + Potato treatment and higher BCR (3.79) than other intercrop treatments.